Analisis Kinerja Keuangan Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Sebelum Dan Sesudah Akuisis - Hamzah Mubarok; Muhamad Yudi Aliudin; Wildan Ma’arif; Riki Gana Suyatna (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to analyze differences in company financial performance before and after making acquisitions in companies listed on the Indonesia Stock Exchange (BEI) which are proxied by the financial ratios Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Earning Per Share (EPS). This research was conducted using quantitative methods by taking data from all companies that reported their acquisition activities to the Business Competition Supervisory Commission (KPPU) in 2014 and were listed on the Indonesia Stock Exchange (BEI). The sampling technique in this research used a purposive sampling method and 10 companies were selected as samples. The period used in this research is 2 years before and 2 years after the acquisition. This research uses three data analyzes, namely descriptive statistical tests, normality tests using the One Sample Kolmogorov-Smirnov method, and hypothesis testing with non-parametric tests using the Wilcoxon Signed Rank Test. The results of the partial test using the Wilcoxon Signed Rank Test showed that there were differences in the ROA and EPS ratios in several comparison periods. Meanwhile, the CR and DER ratios did not show any differences in all comparison periods.